Determination of Repurchase Interest through Consumer Trust: Analysis of Celebrity Endorsement for Scarlett Whitening skincare products - Reni Silviah (Green Publisher, 2024)
This article discusses the influence of celebrity endorsements, through interest in repurchasing Scarlett skincare, on consumer trust in the Tiktok online shop. The objects used are students at Bhayangkara University, Jakarta Raya. The sample used in this research was 200 respondents. In this research, quantitative methods are used with a descriptive approach, the data collection techniques used by researchers are secondary data and primary data. Based on the conceptual framework created, it can be concluded that the hypothesis is that online customer reviews influence consumer trust and repurchase interest, and consumer trust influences repurchase interest.